Winning And Sustaining Space For Civil Society In Semi-authoritarian Settings: What Works And What Doesn’t Work - the Case Of Uganda - Nkwatsibwe, Chris (Graduate School of Development Policy and Practice, 2020)
Over the past decade, the world has witnessed significant changes in global and national polities. These changes, which include the re-emergence of semi-authoritarian regimes have had a substantial effect on the space for civil society advocacy. In Uganda, there has been an undulation between the promising eras of democratization in the 1990s to low days of oppressive legislations and institutions since 2005. What these changes dictate is that stakeholders working within and outside of the state ought not only to change their approach and strategies to cope with the changes in the rules of engagement but also win and sustain their operating space. This paper explores strategies employed by civil society actors to win and sustain space for operation in Uganda’s semi-authoritarian setting. The analysis is situated in Uganda’s Semi-Dominant Neo-Patrimonial Space, characterized by patronage and party dominance. Two case studies from civil society advocacy have been explored to delineate key lessons for civil society advocacy across the world. The case studies are presented in periodized interactions between the state and NGOs in order to contrast the outcomes of different strategies which predominated in different eras. The evidence presented shows that where civil society organizations and actors used more collaborative strategies and techniques in their advocacy, they achieved advocacy results and goals. One the other hand, where civil society engaged through less collaborative and confrontational strategies, they did not achieve results. It follows from the analysis therefore that in semi-authoritarian political settings, where civil society is relatively powerless, change cannot be achieved in ways that are contradictory and conflictual to the interests of a dominant regime. As such, incremental collaborative changes are more preferable and more effective than confrontational change options. The scope and extent of incremental changes would be larger the more collaborative is the civil society engagement.